Self medication practice and associated factors at the regional hospital Bamenda, Cameroon: a prospective study - Teke, Gerald Ngo; Nde, Sirri Letisia; Suh, Mary Bi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Due to paucity of studies on the prevalence and pattern of self medication among Cameroonians and particularly dwellers of Bamenda City, in this research was undertaken to study the practice of self-drug administration among adult out patients at the Regional Hospital Bamenda; identify potential factors influencing self-medication practices; sources of drugs and/or information about medications and finally the reasons for self-drug administration. Methods: Participants (200) of age 18 years and above who came for external consultation during the study period were sampled conveniently after giving their consent. They were administered questionnaires on self-medication practices. Data was analyzed using SPSS version 19.0. Results: The prevalence of self-medication in this study was 86.50% (173/200). The females were more involved in the practice of self-medication (88.18%) than males (85.54%). Participants from deferent occupations had used various classes of drugs through self initiative. Analgesics were most commonly used (84.39%). This was followed by antimalarials (52.60%) and antibiotics (41.62%). While the least represented was the class of laxatives (1.73%). The factors promoting self medication practices were mainly due to mild nature of illness (36.50%) and longtime spent to see the doctor (22.50%). The leading source of information on self-medication prescription and administration came from doctors (78.61%) and pharmacists (34.42%). Over the counter drugs were the most commonly purchased from private pharmacies (76.88%). Conclusions: Self-medication is an important health issue in this area. This study shows the necessity to educate the public on health education and make regulation of pharmacies in limiting self-medication practices.